CHARACTER VALUES ADDRESSED IN STUDENT’S ENGLISH TEXTBOOK OF EIGHT GRADE BASED ON K 13 CURRICULUM - Widia Septrisna; Eliza Eliza; Widya Syafitri (ELP (Journal of English Language Pedagogy), 2019)
This article is written based on a research that has been conducted. This research aimed to analyze the character values ​​found in the textbook used in the 8th grade of the Junior high School "When English Rings a Bell". This research applied the content analysis method with a qualitative approach. Researcher used document, namely a textbook as research instrument. There were six steps in analyzing data: unitizing, sampling, recording / coding, reducing, inferring, and narrating. The results of the analysis showed that in general the eighteen character values ​​were used in the book. However, the character values were still not evenly distributed. Character value ​​that often appear was communicative value, while the character value ​​that appear the least was religious value.